Prevalência da violência intrafamiliar contra adolescentes no Brasil antes, durante e após isolamento social da pandemia da Covid-19 - Cordeiro, Regina Rigoletto (Universidade Federal de São Carlos, 2024)
The social isolation imposed by the COVID-19 pandemic exposed many adolescents to situations of vulnerability within their own homes, particularly regarding the risk of experiencing intrafamilial violence. The reduction in social interactions and the distancing from support networks, such as schools and health services, hindered the detection and reporting of violence cases, suggesting underreporting during the isolation period. In this context, it is deemed essential to analyze and compare notification data during these periods. Accordingly, this research aimed to analyze the prevalence of intrafamilial violence against adolescents in Brazil, covering the period from January 2018 to December 2022. This was a quantitative, exploratory-descriptive, and documentary study. The database used was the Sistema de Informação de Agravos de Notificação (SINAN), specifically analyzing data from seven states: São Paulo, Rio de Janeiro, Rio Grande do Sul, Ceará, Pará, Amazonas, and the Federal District. Through descriptive and correlation analyses, 65,809 notifications of violence against adolescents during the specified period were examined. The variables of interest included: Federative Unit (UF); victims' age; race/skin color; sex; type of violence; means of aggression; relationship between the victim and the perpetrator; location and zone of occurrence; and suspicion of alcohol use. The analyzed periods were subdivided into "pre social isolation caused by the COVID-19 pandemic," "during isolation," and "post-isolation," enabling the assessment of the pandemic's impact on violence notifications against this group. The results indicated a reduction in notifications during isolation, followed by an increase in the post-isolation period. This pattern was observed among both girls and boys, although female victims were more prevalent. Age group analysis revealed that adolescents aged 13 and 14 were most affected by intrafamilial violence, highlighting increased vulnerability during this stage of adolescence. Similarly, data on ethnicity showed that Black and mixed race adolescents were disproportionately affected, with an increase in cases during social isolation. This finding underscores the existence of racial disparities in the incidence and reporting of violence, calling for an intersectional approach in prevention and protection policies. The study also found that physical violence was the most prevalent type, although it decreased during the isolation period, while sexual violence saw a significant increase. Moreover, the analysis of location and victim-perpetrator relationships revealed that most assaults occurred in domestic settings, with an increase in cases involving stepfathers and boyfriends during social isolation. Regarding states, Pará and Ceará experienced an increase in notifications during isolation, while Rio Grande do Sul showed a decline. These findings emphasize the importance of continuously monitoring violence against adolescents in Brazil and developing targeted interventions that consider variations in age, gender, ethnicity, and other vulnerability factors, particularly during catastrophic events such as the COVID-19 pandemic. Continuation of this research is crucial to inform effective public policies aimed at preventing and mitigating the impacts of violence against adolescents, especially during crises and emergencies.
Prevalence of intrafamilial violence against adolescents in Brazil before, during, and after the social isolation of the Covid-19 pandemic
Keywords: Violência intrafamiliar; Covid-19; Adolescentes; Notificações; Intrafamilial violence; Adolescents; Notifications; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO DESENVOLVIMENTO HUMANO